2016
DOI: 10.1177/1524839916673606
|View full text |Cite
|
Sign up to set email alerts
|

Home Gardening and the Health and Well-Being of Adolescents

Abstract: Background:The current paper explores the associations between home gardening and dietary behaviours, physical activity, mental health and social relationships among secondary school students in New Zealand.Methods: Data were drawn from a national youth health and wellbeing survey, conducted in 2012. In total, 8500 randomly selected students from 91 randomly selected secondary schools completed the survey.Results: Two thirds of students had a vegetable garden at home and one quarter of all students participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 30 publications
6
30
0
2
Order By: Relevance
“…Local school and community partners, who have worked with the authors, shared observations and comments related to school connectedness, improved self-esteem, feeling safe in school gardens and mental well-being about students who were involved in school garden and food literacy activities. While similar observations have been noted in other locations including the USA [1], New Zealand [10], Australia [11] and Greece [11] no local research data was available, particularly from a youth perspective.…”
Section: Introductionsupporting
confidence: 63%
“…Local school and community partners, who have worked with the authors, shared observations and comments related to school connectedness, improved self-esteem, feeling safe in school gardens and mental well-being about students who were involved in school garden and food literacy activities. While similar observations have been noted in other locations including the USA [1], New Zealand [10], Australia [11] and Greece [11] no local research data was available, particularly from a youth perspective.…”
Section: Introductionsupporting
confidence: 63%
“…Besides cultivating and trying to be partially self-sufficient for fruit and vegetables (that are expensive and hard to find now), this could give me psychological benefits. There is an association between home gardening and physical and mental well-being, and this has been demonstrated for various categories of people at risk (Grabbe et al 2013;van Lier et al 2017;John et al 2016;Quick et al 2017). I had a lot of material in my garage, some pipes, shelves, supports, other stuff, and hardware.…”
Section: Introductionmentioning
confidence: 96%
“…However, the limitation of this study is the lack of a no-treatment control group for the comparison of the effects of gardening. In a survey study, home gardening was found to be positively correlated with improved mental health and well-being [75]. Adolescents who did home gardening reported fewer depressive symptoms and improved emotional well-being than those who did not do gardening.…”
Section: Well-beingmentioning
confidence: 96%